2011
DOI: 10.1099/mic.0.043075-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the phenazine-inducing protein Pip in stress resistance of Pseudomonas chlororaphis

Abstract: The triggering of antibiotic production by various environmental stress molecules can be interpreted as bacteria's response to obtain increased fitness to putative danger, whereas the opposite situation – inhibition of antibiotic production – is more complicated to understand. Phenazines enable Pseudomonas species to eliminate competitors for rhizosphere colonization and are typical virulence factors used for model studies. In the present work, we have investigated the negative effect of subinhibitory concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
2
9
2
Order By: Relevance
“…Reductions in the cellular yields of the wild-type and 30-84MiaA that occurred when the RpeA/RpeB regulation was bypassed via constitutive expression of pip or rpeB indicated that RpeB regulation of Pip is important for limiting phenazine production at the expense of optimal growth, as well as in curtailing phenazine biosynthesis under suboptimal growth conditions. Previous work using P. chlororaphis PCL1391 demonstrated that constitutive expression of pip restored phenazine production under stressful abiotic conditions that were repressive to phenazine production, but sufficient for QS, such as sub-inhibitory concentrations of fusaric acid or NaCl; however, similar to our study, this resulted in further reductions in cellular yields [23]. Their observations support the model that phenazine biosynthesis is constrained under poor growth conditions and that Pip regulation is important for this control; however, the regulators of Pip were not identified [23].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Reductions in the cellular yields of the wild-type and 30-84MiaA that occurred when the RpeA/RpeB regulation was bypassed via constitutive expression of pip or rpeB indicated that RpeB regulation of Pip is important for limiting phenazine production at the expense of optimal growth, as well as in curtailing phenazine biosynthesis under suboptimal growth conditions. Previous work using P. chlororaphis PCL1391 demonstrated that constitutive expression of pip restored phenazine production under stressful abiotic conditions that were repressive to phenazine production, but sufficient for QS, such as sub-inhibitory concentrations of fusaric acid or NaCl; however, similar to our study, this resulted in further reductions in cellular yields [23]. Their observations support the model that phenazine biosynthesis is constrained under poor growth conditions and that Pip regulation is important for this control; however, the regulators of Pip were not identified [23].…”
Section: Discussioncontrasting
confidence: 52%
“…Additionally, it was proposed that RpoS may regulate Pip in response to nutrient conditions, since constitutive expression or mutation of rpoS can alter pip expression and phenazine production under different medium conditions [16,18,22]. Moreover, RpoS regulation of phenazine production is plausible since phenazine production is correlated with the expression of RpoS-regulated genes important for oxidative stress response [9,23]. Pip has been shown to be involved in the curtailment of phenazine production in response to other abiotic stresses (fusaric acid, kanamycin or NaCl) hypothetically to conserve resources for stress management, although RpoS did not affect Pip levels under these stress conditions [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the hypothesis that RpeA may function as a sensor of the metabolic state or stress condition of the cell, determining whether production of secondary metabolites is appropriate (Whistler & Pierson, 2003). A recent study showed that pip overexpression in PCL1391 is detrimental to cells under various stress conditions (Girard & Rigali, 2011), leading to the speculation that Pip may modulate biological functions (such as phenazine production) that may be deleterious to the cell under stressed conditions. In this study, stresses could reduce pip expression, but not the expression of the alternate sigma factor rpoS, which can influence pip expression in vitro.…”
Section: Discussionmentioning
confidence: 47%
“…Although the exact targets of Pip remain unclear, Pip has been shown to promote phenazine production by enhancing phzI and phzR expression. A recent study demonstrated that switching off phenazine synthesis by attenuating pip expression enhanced bacterial survival, suggesting that Pip plays a role in stress response (Girard & Rigali, 2011).…”
Section: Introductionmentioning
confidence: 99%